PERSEPSI MASYARAKAT PESISIR TERHADAP KEPEMIMPINAN PEREMPUAN NELAYAN DI PULAU PRAMUKA KEPULAUAN SERIBU - Ikhsan Fuady; Titien Yusnita (Indonesian Journal of Agricultural Economics, 2016)
Fishing profession is a profession that demands physical strength and mental toughness. The livelihood of fishermen in processing marine resources is highly dependent on natural conditions are unstable. Therefore, the fishermen's wives who is better known as female fishermen will diversify the profession as a survival strategy. Public perception of female fishers very interesting to study, given in Pramuka Island Thousand Islands, many women believed fishermen community to hold the post of RT (neighborhood) and untukmendapat nickname as' ruler daratan'.Tujuan this study to determine the perception of coastal communities against female leadership fishermen and reviewing the division of tasks (division of labor) in the coastal fishing households in Pramuka Island Thousand Islands.This study used a qualitative method with descriptive approach using observation and interviews with 25 people fisher woman and her husband who works as a fisherman and the local village chief. The results of this study indicate that: (1) a paradigm shift towards female leadership that women more fishers believed served as Chairman of RT, (2) the opinion of women is very influential in decision-making at home and in social life, (3) the division of tasks (division of labor ) in households where the wife impartial fisherman to take over portions of greater responsibility than men husband remembering the fishermen longer at sea than on land.